2020
DOI: 10.1007/s42690-020-00120-z
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient composition of the Indonesian sago grub (Rhynchophorus bilineatus)

Abstract: The sago grub (Rhynchophorus bilineatus) [Montrouzier, Coleoptera, Dryophthoridae] is a local delicacy in the Papua Province in Indonesia. In this study, the nutrient content of the edible insect was measured using chromatographic and spectrometric methods. The results showed that it contains 10.39 g protein and 17.17 g oil/ 100 g fresh weight. The sago grub meets the FAO/ WHO requirements of 40% essential amino acids and a 0.60 ratio between essential to non-essential amino acids. Its limiting amino acid is m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 31 publications
1
15
0
2
Order By: Relevance
“…However, when provided with a cadmium free diet, concentrations fell rapidly (Kramarz, 1999). The cadmium concentration in the sago grub was below 10% of the dietary concentration (Köhler et al, 2020) and no evidence of cadmium or zinc accumulation was found in the beetle Neochetina eichhorniae (Jamil and Hussain, 1992).…”
Section: Minerals and Heavy Metalsmentioning
confidence: 98%
“…However, when provided with a cadmium free diet, concentrations fell rapidly (Kramarz, 1999). The cadmium concentration in the sago grub was below 10% of the dietary concentration (Köhler et al, 2020) and no evidence of cadmium or zinc accumulation was found in the beetle Neochetina eichhorniae (Jamil and Hussain, 1992).…”
Section: Minerals and Heavy Metalsmentioning
confidence: 98%
“…In the fight against malnutrition, there are three possible options: fortification, supplementation and dietary diversification. Among the three, dietary diversification is viewed as most sustainable [3]. In promoting this option, the FAO encourages people to utilize indigenous fruits and vegetables to increase the nutrients in their diet.…”
Section: Resultsmentioning
confidence: 99%
“…The Province is divided into lowlands consisting of sago and mangrove forests, grasslands, and swamps in the coastal areas, and upland areas with primary and secondary forests, and farmed plots. Due to limited agricultural resources in the area, insects, especially grasshoppers, leaf and stick insects, cicadas and large moths and their caterpillars, remain as important protein sources in the people's daily diet [3].…”
Section: Introductionmentioning
confidence: 99%
“…Sagu merupakan salah satu pangan lokal sumber karbohidrat dan limbah panen sagu menghasilkan ulat sagu sebagai sumber protein (Nirmala et al, 2017). Penelitian tentang komposisi gizi ulat sagu dari Papua memiliki label protein tinggi yaitu 10,39/100 g, nilai cerna 92%, tinggi kandungan magnesium dan zink, dan tingkat logam berat yang aman (Köhler et al, 2020). Penelitian ulat sagu pada subjek balita sehat di Sulawesi menunjukkan adanya peningkatan berat badan dan tinggi badan setelah intervensi ulat sagu sebanyak 20 g yang diversifikasi pada makanan pendamping air susu ibu (ASI) (Nirmala et al, 2017).…”
Section: Pendahuluanunclassified